PROSPECTS OF DIGITAL BANKING IN UZBEKISTAN - Nizomova Mehrangiz Jamoliddinzoda; Tuxtayeva Bahor Rashid kizi (Scholar Express Journal, 2022)
In this article, digital banking services, which are a part of the digital industry, are analyzed both theoretically and practically
Keywords: Digital economy; digital finance; e-banking